Trends in National Institutes of Health-Funded Congenital Heart Disease Research from 2005 to 2015 - Burns, Kristin M. (Pediatr Cardiol, 2017)
In an era of ongoing need for research to enable evidence-based care for the expanding population with congenital heart disease (CHD), economic fluctuations have impacted research funding. We characterize trends in NIH-funded CHD research from 2005 to 2015. We searched the NIH RePORTER database from 2005 to 2015 using the terms “congenital heart” and “cardiac morphogenesis”. Projects were characterized by year, institute, mechanism, costs, type and topic, and funding trends were analyzed. From 2005 to 2015, NIH funded 633 CHD research projects with total costs of $991 million. The National Heart, Lung, and Blood Institute funded 83% of CHD projects (528, $857 million). The R01 mechanism was used for 45% of projects (288, $421 million). Projects were 70% basic/early translational research, 27% clinical research, and 3% both. Cardiac developmental biology was the most common topic (52%), followed by technology/therapy development (15%), and diagnosis/management (12%). The total number of CHD projects ranged from 153 to 221 per year (30–58 new projects/year), and costs per year ranged from $58 to $116 million. The number of projects and total costs increased until 2012, but decreased again thereafter. CHD research did not experience as much erosion as overall NIH purchasing power; in constant dollars, CHD research funding levels in 2015 were $12 million higher than those in 2005. The NIH supported a diverse portfolio of CHD projects from 2005 to 2015. Support of CHD research projects trended upward until 2012, but declined thereafter due to fiscal austerity measures.